Els parlars de transició entre el català occidental i l'oriental - Navarro, Pere (Caplletra. Revista Internacional de Filologia, 1999)
Traditionally, the Catalan language has been divided into two great dialectal area: West and East. It was Milà i Fontanals who first established in 1861 such classification of Catalan dialects, based on the criterion of unstressed vowels: the Western dialects keepa, e and o in unstressed syllables, whereas Eastern dialects have evolved into the neutral vowel.Once these criteria have been applied, it has been found that the isoglosses built on the three phonetic phenomena described above are not superimposed, and therefore do not coincide. As the differences in isoglosses increase if we consider the criteria proposed by Veny in «Els parlars catalans», we may infer that the transition from one set of dialects to the other takes place without any sudden change of features; in other words, there are no clear boundaries between the two dialectal areas.This paper intends to supply data on the southern transition area between the Western and Eastern dialects, covering the areas of Ribera d'Ebre, Priorat, Baix Camp and Conca de Barberà.